GEN-Z'S CONSUMPTIVE BEHAVIOR TOWARDS THE TREND OF YOU LIVE ONLY ONCE TO YOU NEED ONLY ONE IN THE PERSPECTIVE OF ISLAMIC BUSINESS ETHICS - Anggraini, Misi (UIN Raden Mas Said Surakarta, 2025)
This study explores the shift in consumptive behaviour among Generation Z from the